STUDING OF THE THEORY OF CHEMICAL STRUCTURE OF ORGANIC COMPOUNDS IN SECONDARY SCHOOLS: METHODOLOGICAL ASPECTS - Grabovyy, Andrii K. (Educological discourse, 2016)
The study examined the theoretical and methodological foundations for improving methods of studying the theory of chemical structure of organic compounds in secondary schools, the level of standart. Theoretical analysis of the literature on the study showed that the problem is urgent and requires further research. The basic of the theory of chemical structure of organic compounds A. Butlerova and methodological aspects of the study. It is shown that the leading means of learnig the basic assumptions of the theory of chemical structure of organic compounds are chemical experiment in conjunction with iconic model.